High-conductivity low-silver-content low-temperature composite polymer conductive silver paste and preparation method thereof
By using polyhedral silver-covered copper powder, submicron spherical silver powder and sheet silver powder under low temperature conditions, combined with the ratio of mixed resin and solvent, a low-temperature composite polymer conductive silver paste with high conductivity and low silver content was prepared, and the solution was solved The complex process and high temperature problems in the prior art have achieved efficient conductive performance and cost reduction.
Patent Information
- Application Number
- CN202411381757.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-17
AI Technical Summary
In the prior art, when preparing electrode silver paste with high conductivity and low silver content, the process is complex, time-consuming and requires high temperature. Polyol-based welding additives will increase the viscosity and bubble risk of the slurry, affecting the electrode performance.
Polyhedral silver-clad copper powder is used instead of sterling silver powder, combined with sub-micron spherical silver powder and sheet-shaped silver powder, and prepared high-conductive, low-silver content low-temperature composite polymer conductive silver paste through low-temperature mechanical stirring and three-roll mill rolling to avoid using melt welding The auxiliary agent uses the high surface area structure of polyhedral silver-covered copper powder to reduce the contact resistance between particles, and improves bonding and temperature and corrosion resistance through the combination of mixed resin and low-boiling and medium-boiling solvents.
The preparation of low-temperature composite polymer conductive silver paste with high conductivity and low silver content is achieved, which reduces production costs, improves conductivity and temperature and corrosion resistance, reduces the number of pores in the conductive film after curing, and improves electrical performance.
Smart Images

Figure BDA0005070071790000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heterojunction solar cells, and in particular relates to a low-temperature composite polymer conductive silver paste with high conductivity and low silver content and a preparation method thereof. Background Art
[0002] As the 0BB process penetrates into the electrode silver paste of HJT cells (heterojunction solar cells), micron-sized spherical silver-coated copper powder partially replaces high-compacted flake silver powder and is favored by capital. According to research, silver-copper composite powder not only has excellent electrical and thermal conductivity, but also the copper core and silver shell structure can effectively reduce the electromigration of pure silver paste in high temperature and humid environment, which leads to short circuit failure of electronic components. At the same time, silver-coated copper powder with low silver content can greatly reduce the price of electronic paste. Therefore, the use of low silver content silver-coated copper powder as conductive filler has great economic value and application value.
[0003] The application publication number CN 116844778A uses silver-plated glass powder and graphene microsheets as partial conductive fillers, and prepares a conductive silver paste with a fineness of 5 um, a room temperature viscosity of 35,000 centipoise, and a conductivity of 100 S / m through secondary mixing-reaction-rolling of the conductive silver paste. However, the process for preparing the silver paste is not only complicated and time-consuming, but also requires a high temperature of 1300°C to prepare the silver-plated glass powder, which greatly limits the application of this solution.
[0004] CN 117198591A uses silver-coated copper powder with smooth surface and high sphericity to completely replace flaky silver powder and is used together with small-particle spherical silver powder as a conductive seasoning, and then mixed with a carrier to prepare n-HJT battery electrode silver paste. However, the polyols used as welding aids have great limitations. Adding this type of aid to bisphenol resin often increases the viscosity of the paste, accelerates the emulsification of the paste after long-term placement, and increases the risk of foaming during the paste drying process. At the same time, this solution uses silver-coated copper powder with high sphericity as a substitute for flaky silver powder. Since the spherical silver powder is accumulated in the paste by point contact, it often has a large contact resistance. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing a low-temperature composite polymer conductive silver paste with high conductivity and low silver content, which can prepare a low-temperature composite polymer conductive silver paste with high conductivity and low silver content without the need for a welding aid.
[0006] The second object of the present invention is to provide a low-temperature composite polymer conductive silver paste with high conductivity and low silver content.
[0007] In order to achieve one of the above purposes, the present invention adopts the following technical solution:
[0008] A method for preparing a low-temperature composite polymer conductive silver paste with high conductivity and low silver content, the preparation method comprising:
[0009] Step S1, adding a polymer resin and a coupling agent into an organic solvent, and mechanically stirring the mixture for 5 to 15 minutes at a temperature of 25 to 30° C. to obtain an organic carrier;
[0010] In the step S1, the mass ratio of the polymer resin, the coupling agent and the organic solvent is 12-18:1:7-10;
[0011] The polymer resin is a mixture of two or more of epoxy resin, phenolic resin, ethyl cellulose, silicone resin and polyacrylic acid resin;
[0012] The organic solvent is a mixture of a low boiling point solvent and a medium boiling point solvent;
[0013] Step S2, mixing polyhedral silver-coated copper powder, submicron spherical silver powder, flaky silver powder and organic carrier in a mass ratio of 55-65:5-15:3-13:17-27, and mechanically stirring at a temperature of 25-30° C. for 5-15 minutes to obtain a mixed silver paste;
[0014] Step S3, rolling the mixed silver paste through a three-roll mill to obtain a low-temperature composite polymer conductive silver paste with high conductivity and low silver content;
[0015] In step S3, the rolling process conditions are as follows: the rolling temperature is 25-35°C, the rolling is repeated three times, and the spacing between the coarse and fine rolls is 15-20um, 10-15um and 7.5-10um respectively.
[0016] Further, in the step S1, the coupling agent is at least one of the silane coupling agents KH-590, KH-570, KH-560, and KH-550;
[0017] The low boiling point solvent is one of ethers, ketones, halogenated alkanes and alcohols;
[0018] The medium boiling point solvent is one of citric acid esters, divalent acid esters and aromatic hydrocarbons.
[0019] Furthermore, in the step S1, the epoxy resin is one of bisphenol A epoxy resin and bisphenol F epoxy resin;
[0020] The silicone resin monomer is at least one of dimethyldichlorosilane, phenyltrichlorosilane, methylphenyldichlorosilane, methyltrichlorosilane and methoxyphenyldichlorosilane.
[0021] Further, in the step S1, the ether is one of furan, methyl tert-butyl ether, diethyl ether and diisopropyl ether;
[0022] The ketone is one of acetone and butanone;
[0023] The halogenated alkane is one of chloroform, dichloromethane and dichloroethane;
[0024] The alcohol is one of methanol, ethanol, n-propanol and isopropanol;
[0025] The citrate ester is one of triethyl citrate, tripropyl citrate and tributyl citrate;
[0026] The divalent ester is a divalent acid ester reagent DBE;
[0027] The aromatic hydrocarbon is one of xylene, toluene, p-methoxybenzene and o-xylene.
[0028] Furthermore, in step S2, the average particle size of the polyhedral silver-coated copper powder is 3.5-4.5 μm, and the tap density is >4.2 g / cm 3 , the specific surface area is 0.15~0.25m 2 / g, silver content is 8%-15%;
[0029] The average particle size of the submicron spherical silver powder is 0.2-0.5um, and the tap density is >2g / cm 3 , with a specific surface area of 1.1 to 2.9 m 2 / g;
[0030] The average particle size of the flaky silver powder is 2.0 to 5.0 μm, and the tap density is 1.8 to 3.0 g / cm 3 , with a specific surface area of 0.7 to 1.4 m 2 / g.
[0031] Furthermore, in step S3, the rotation speed of the feed roll of the three-roll mill is 30-50 rpm, the rotation speed of the middle roll is 70-100 rpm, and the rotation speed of the discharge roll is 100-200 rpm.
[0032] In order to achieve the second objective above, the present invention adopts the following technical solution:
[0033] A low-temperature composite polymer conductive silver paste with high conductivity and low silver content is prepared by the above-mentioned preparation method.
[0034] Furthermore, the sheet resistance of the low-temperature composite polymer conductive silver paste is 12.51-28.26 mΩ / □, and the silver content is 12-38 wt%.
[0035] In summary, the technical solution of the present invention has the following technical effects:
[0036] The polyhedral silver-coated copper powder of the present invention replaces the pure silver powder, which not only realizes the effective replacement of the base metal copper for the precious metal silver, but also reduces the silver content in the slurry and reduces the production cost; the present invention adopts the polyhedral silver-plated copper powder with a rough surface as the conductive filler, and under the premise of not needing a welding auxiliary agent, utilizes the high surface area structure unique to the polyhedral silver-coated copper powder to convert the stacking mode between the particles from point contact to line contact and surface contact, thereby reducing the contact resistance between the particles and improving the conductivity of the conductive silver paste; the present invention adopts two or more mixed resins, so that the mixed resin has excellent bonding strength and flexibility, and can improve the heat resistance and corrosion resistance of the slurry, and at the same time, the mixed resin can act as a curing agent, so that no additional curing agent needs to be added during the slurry preparation process; the present invention adopts a combination of a low-boiling point solvent and a medium-boiling point solvent to form a stepwise volatilization effect, which reduces the number of unclosed pores in the conductive film after curing, promotes the densification degree of the conductive path, and improves the electrical properties of the slurry. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Embodiment 1:
[0039] 1. Add the polymer resin and the coupling agent to the organic solvent, stir mechanically for 10 minutes at a temperature of 28°C until the mixture is uniformly mixed, and obtain an organic carrier. The mass ratio of the polymer resin, the coupling agent and the organic solvent is 15:1:9. The polymer resin includes bisphenol A epoxy resin and phenolic resin, and the mass ratio of bisphenol A epoxy resin and phenolic resin is 8:5.2. The coupling agent is silane coupling agent KH-570. The organic solvent includes tributyl citrate and acetone, and the mass ratio of tributyl citrate and acetone is 5.32:2.6.
[0040] 2. Mix the polyhedron silver-coated copper powder, submicron spherical silver powder, flaky silver powder and organic carrier in a mass ratio of 60:10:8:20, and mechanically stir for 10 minutes at a temperature of 28° C. until the mixture is uniformly mixed to obtain a mixed silver paste.
[0041] Among them, the average particle size of the polyhedron silver-coated copper powder is 4.0um, and the tap density is 4.4g / cm 3 , with a specific surface area of 0.20m 2 / g, silver content is 12%. The average particle size of submicron spherical silver powder is 0.4um, and the tap density is 2.2g / cm 3 , with a specific surface area of 2.0m 2 / g. The average particle size of the flaky silver powder is 3.0um and the tap density is 2.4g / cm 3 , with a specific surface area of 1.0m 2 / g.
[0042] 3. The mixed silver paste is rolled and refined through a three-roll mill to obtain a composite polymer conductive silver paste with a silver content of 25.2%. The rolling temperature is 30°C, and the rolling is continuous for three times, and the spacing between the coarse and fine rollers for the three times is 18um, 12um and 8.5um respectively. The speed of the feed roller of the three-roll mill is 40rpm, the speed of the middle roller is 85rpm, and the speed of the discharge roller is 150rpm.
[0043] Embodiment 2:
[0044] 1. Add the polymer resin and the coupling agent to the organic solvent, stir mechanically for 5 minutes at a temperature of 25°C until the mixture is uniformly mixed, and obtain an organic carrier. The mass ratio of the polymer resin, the coupling agent and the organic solvent is 12:1:7. The polymer resin includes ethyl cellulose and phenolic resin, and the mass ratio of ethyl cellulose to phenolic resin is 6.56:4. The coupling agent is silane coupling agent KH-560. The organic solvent includes tripropyl citrate and ethylene dichloride, and the mass ratio of tripropyl citrate to ethylene dichloride is 5:1.16.
[0045] 2. Mix the polyhedron silver-coated copper powder, submicron spherical silver powder, flaky silver powder and organic carrier in a mass ratio of 55:5:3:17, and mechanically stir for 5 minutes at a temperature of 25° C. until the mixture is uniformly mixed to obtain a mixed silver paste.
[0046] Among them, the average particle size of the polyhedron silver-coated copper powder is 3.5um, and the tap density is 4.3g / cm 3 , with a specific surface area of 0.15m 2 / g, silver content is 8%. The average particle size of submicron spherical silver powder is 0.2um, and the tap density is 2.1g / cm 3 , with a specific surface area of 1.1m 2 / g. The average particle size of the flaky silver powder is 2.0um and the tap density is 1.8g / cm 3 , with a specific surface area of 0.7m 2 / g.
[0047] 3. The mixed silver paste is rolled and refined by a three-roll mill to obtain a composite polymer conductive silver paste with a silver content of 12.4 wt%. The rolling temperature is 25°C, and the rolling is continuous for three times, and the spacing between the coarse and fine rollers for the three times is 15um, 10um and 7.5um respectively. The speed of the feed roller of the three-roll mill is 30rpm, the speed of the middle roller is 70rpm, and the speed of the discharge roller is 70rpm.
[0048] Embodiment 3:
[0049] 1. Add the polymer resin and the coupling agent to the organic solvent, stir mechanically for 15 minutes at a temperature of 30°C until the mixture is uniformly mixed, and obtain an organic carrier. The mass ratio of the polymer resin, the coupling agent and the organic solvent is 18:1:10. The polymer resin includes bisphenol F epoxy resin and polyacrylic acid resin, and the mass ratio of bisphenol F epoxy resin and polyacrylic acid resin is 7.54:8.3. The coupling agent is silane coupling agent KH-550. The organic solvent includes dibasic acid ester DBE and furan, and the mass ratio of dibasic acid ester DBE and furan is 8.1:0.7.
[0050] 2. Mix the polyhedron silver-coated copper powder, submicron spherical silver powder, flaky silver powder and organic carrier in a mass ratio of 65:15:13:27, and mechanically stir for 15 minutes at a temperature of 30° C. until the mixture is uniformly mixed to obtain a mixed silver paste.
[0051] Among them, the average particle size of the polyhedron silver-coated copper powder is 4.5um, and the tap density is 4.5g / cm 3 , with a specific surface area of 0.25m 2 / g, silver content is 15%. The average particle size of submicron spherical silver powder is 0.5um, and the tap density is 2.4g / cm 3 , with a specific surface area of 2.9m 2 / g. The average particle size of the flaky silver powder is 5.0um and the tap density is 3.0g / cm 3 , with a specific surface area of 1.4m 2 / g.
[0052] 3. The mixed silver paste is rolled and refined by a three-roll mill to obtain a composite polymer conductive silver paste with a silver content of 37.75%. The rolling temperature is 35°C, and the rolling is continuous for three times, and the spacing between the coarse and fine rollers is 20um, 15um and 10um respectively. The feed roller speed of the three-roll mill is 50rpm, the middle roller speed is 100rpm, and the discharge roller speed is 100rpm.
[0053] Table 1 Performance indicators of low temperature composite polymer conductive silver paste of Examples 1 to 3
[0054]
[0055] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a low-temperature composite polymer conductive silver paste with high conductivity and low silver content, characterized in that: The preparation method comprises: Step S1, adding a polymer resin and a coupling agent into an organic solvent, and mechanically stirring the mixture for 5 to 15 minutes at a temperature of 25 to 30° C. to obtain an organic carrier; In the step S1, the mass ratio of the polymer resin, the coupling agent and the organic solvent is 12-18:1:7-10; The polymer resin is a mixture of two or more of epoxy resin, phenolic resin, ethyl cellulose, silicone resin and polyacrylic acid resin; The organic solvent is a mixture of a low boiling point solvent and a medium boiling point solvent; Step S2, mixing polyhedral silver-coated copper powder, submicron spherical silver powder, flaky silver powder and organic carrier in a mass ratio of 55-65:5-15:3-13:17-27, and mechanically stirring at a temperature of 25-30° C. for 5-15 minutes to obtain a mixed silver paste; Step S3, rolling the mixed silver paste through a three-roll mill to obtain a low-temperature composite polymer conductive silver paste with high conductivity and low silver content; In step S3, the rolling process conditions are as follows: the rolling temperature is 25-35°C, the rolling is repeated three times, and the spacing between the coarse and fine rolls is 15-20um, 10-15um and 7.5-10um respectively.
2. The preparation method according to claim 1, characterized in that: In the step S1, the coupling agent is at least one of the silane coupling agents KH-590, KH-570, KH-560, and KH-550; The low boiling point solvent is one of ethers, ketones, halogenated alkanes and alcohols; The medium boiling point solvent is one of citric acid esters, divalent acid esters and aromatic hydrocarbons.
3. The preparation method according to claim 2, characterized in that: In the step S1, the epoxy resin is one of bisphenol A epoxy resin and bisphenol F epoxy resin; The silicone resin monomer is at least one of dimethyldichlorosilane, phenyltrichlorosilane, methylphenyldichlorosilane, methyltrichlorosilane and methoxyphenyldichlorosilane.
4. The preparation method according to claim 3, characterized in that: In the step S1, the ether is one of furan, methyl tert-butyl ether, diethyl ether and diisopropyl ether; The ketone is one of acetone and butanone; The halogenated alkane is one of chloroform, dichloromethane and dichloroethane; The alcohol is one of methanol, ethanol, n-propanol and isopropanol; The citrate ester is one of triethyl citrate, tripropyl citrate and tributyl citrate; The divalent ester is a divalent acid ester reagent DBE; The aromatic hydrocarbon is one of xylene, toluene, p-methoxybenzene and o-xylene.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the average particle size of the polyhedral silver-coated copper powder is 3.5-4.5 μm, and the tap density is >4.2 g / cm 3 , the specific surface area is 0.15~0.25m 2 / g, silver content is 8-15%; The average particle size of the submicron spherical silver powder is 0.2-0.5um, and the tap density is >2g / cm 3 , with a specific surface area of 1.1 to 2.9 m 2 / g; The average particle size of the flaky silver powder is 2.0 to 5.0 μm, and the tap density is 1.8 to 3.0 g / cm 3 , with a specific surface area of 0.7 to 1.4 m 2 / g.
6. The preparation method according to claim 5, characterized in that: In step S3, the rotation speed of the feed roll of the three-roll mill is 30-50 rpm, the rotation speed of the middle roll is 70-100 rpm, and the rotation speed of the discharge roll is 100-200 rpm.
7. A low-temperature composite polymer conductive silver paste with high conductivity and low silver content, characterized in that: The low-temperature composite polymer conductive silver paste is prepared by the preparation method described in any one of claims 1 to 6.
8. The low-temperature composite polymer conductive silver paste according to claim 7, characterized in that: The sheet resistance of the low-temperature composite polymer conductive silver paste is 12.51-28.26 mΩ / □, and the silver content is 12-38%.
Citation Information
Patent Citations
Preparation method of low-silver-content composite conductive silver paste
CN116844778A
Heterojunction silver-coated copper slurry with high oxidation resistance and preparation process thereof
CN117198591A